KONTRIBUSI GURU AKIDAH AKHLAK DALAM MEMBENTUK EMPATI DAN KEPEKAAN SOSIAL PESERTA DIDIK KELAS VIII DI MTS DDI MANDING POLEWALI MANDAR - Nurzamsinar; Sudirman; Nurwana; Nur Anisyah; Ridwan (Universitas Islam Negeri Alauddin Makassar, 2025)
Akhlak education plays an important role in shaping students' character, especially in instilling empathy and social awareness. In the midst of the crisis of human values, akhlak teachers have a responsibility not only as teachers, but also as moral role models who integrate Islamic values into learning. The type of research uses qualitative research with a field research approach in the form of descriptive analysis. The data collection techniques used are observation, interviews, and documentation. Furthermore, all data obtained is processed with the stages of data analysis, namely data reduction, data presentation, and data conclusions. The results of the study are the contribution of akhlak teachers in shaping empathy and social awareness of class VIII students at Mts DDI Manding Polewali Mandar, namely through structured teaching based on Islamic values, teachers have succeeded in integrating lessons on empathy and social sensitivity into daily learning activities with the approach used is a moral approach, experience-based learning, and group discussions, to instill the values of empathy and social sensitivity. Practical activities, such as social service and group work, are also used to provide students with direct experience in applying these values.